Cardiopulmonary resuscitation success measured by a short reaction time - Ilić Andrijana (Halo 194)
Introduction/Objective The Emergency Medical Service reaction time is the interval between the moment the Emergency Medical Team is dispatched and the moment they arrive at the patient's side. This paper stresses the importance of a short reaction time and early cardiopulmonary resuscitation (CPR) by comparing two medical cases and data from available literature. Case reports: We are presenting the cases of two elderly patients who had both acquired chest pain that led to acute cardiac arrest (ACA) in outpatient settings. One patient suffered ACA in the presence of the Emergency Medical Team (EMT), who immediately initiated CPR and Advanced Life Support (ALS) measures. Their reaction time was 0 min. The patient was successfully resuscitated and transported to the hospital. Five days later, he had recovered and was discharged to go home. In the second patient's case, ACA occurred in a public place, but the witnesses were not educated to perform Basic Life Support (BLS), so no CPR was initiated before the EMT arrived. Their reaction time was 9 minutes. The CPR measures that they initiated were unsuccessful and the patient was pronounced dead 30 minutes later. Conclusion: A short reaction time and early CPR are crucial for surviving out-of-hospital ACA. The education of non-medical personnel in the early initiation of BLS measures should be insisted upon.